OPTIMALISASI HASIL BELAJAR SISWA MELALUI DISCOVERY LEARNING TERINTEGRASI TEACHING AT THE RIGHT LEVEL (TARL) PADA MATERI PERUBAHAN WUJUD BENDA DI SEKOLAH DASAR - Mahdalena Ulfa; Fatma Zuhra; Fatimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of third-grade students due to conventional teacher-centered learning and a lack of instructional models tailored to students' ability levels, particularly on the topic of changes in the state of matter. This study aimed to improve student learning outcomes, teacher and student activities, and to determine student responses through the implementation of the Discovery Learning model integrated with Teaching at the Right Level (TaRL). This research employed a qualitative approach with Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, acting, observing, and reflecting phases. The subjects were 15 third-grade students at UPTD SD Negeri 16 Peusangan. Data collection techniques included learning outcome tests, teacher and student activity observation sheets, and student response questionnaires. Data were analyzed using quantitative descriptive analysis through percentages of learning mastery, observation scores, and response averages. The results showed that the integration of Discovery Learning and TaRL significantly improved student learning outcomes, increasing classical mastery from 60% in Cycle I to 93.33% in Cycle II. Teacher activity increased from 66.50% in the initial action to 92.50% at the end of Cycle II, reaching the very good category. Student activity also improved from 62.50% to 91.00%, categorized as very good. Furthermore, students exhibited a positive response with an average percentage of 78.20%. It can be concluded that the implementation of Discovery Learning integrated with TaRL is effective in improving student learning outcomes, classroom activity, and student responses on the topic of changes in the state of matter.